2015
DOI: 10.3389/fnhum.2015.00659
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neural Activity in the Temporoparietal Junction with Transcranial Direct Current Stimulation Changes the Role of Beliefs in Moral Judgment

Abstract: Judgments about whether an action is morally right or wrong typically depend on our capacity to infer the actor’s beliefs and the outcomes of the action. Prior neuroimaging studies have found that mental state (e.g., beliefs, intentions) attribution for moral judgment involves a complex neural network that includes the temporoparietal junction (TPJ). However, neuroimaging studies cannot demonstrate a direct causal relationship between the activity of this brain region and mental state attribution for moral jud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 52 publications
9
46
1
Order By: Relevance
“…right). Although there have been several TMS and tDCS studies stimulating rTPJ (Mai et al, 2016;Santiesteban et al, 2012Santiesteban et al, , 2015Sellaro et al, 2015;Sowden et al, 2015;Ye et al, 2015), this is the first study, to our knowledge, reporting an influence of the rTPJ stimulation on performances of deceptive behaviors.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…right). Although there have been several TMS and tDCS studies stimulating rTPJ (Mai et al, 2016;Santiesteban et al, 2012Santiesteban et al, , 2015Sellaro et al, 2015;Sowden et al, 2015;Ye et al, 2015), this is the first study, to our knowledge, reporting an influence of the rTPJ stimulation on performances of deceptive behaviors.…”
Section: Discussionmentioning
confidence: 81%
“…The tDCS was delivered with two saline-soaked surface electrodes (size: 5 × 7 cm 2 ) connected to a constant-current stimulator (DC-STIMULATOR Plus, neuroConn GmbH, Germany). In the rTPJ session, an anodal electrode was placed over central parietal 6 (CP6), according to the international EEG 10/20 system (Santiesteban et al, 2012;Sellaro et al, 2015;Sowden et al, 2015;Ye et al, 2015). A cathodal electrode was positioned over the vertex (Cz) of each participant as a reference.…”
Section: Basic Procedures Of a Tdcs Experimentsmentioning
confidence: 99%
“…Though the impacts of varying protocols are complex (Horvath et al ., ), anodal tDCS generally promotes depolarisation of resting membrane potentials in underlying cortical tissue (increasing rates of neuronal firing), while cathodal tDCS is understood to increase hyperpolarisation and reduce firing rates (Nitsche et al ., ). tDCS studies suggest TPJ modulation can influence performance in tasks involving mentalising (or related constructs such as moral reasoning, cognitive empathy, visual perspective taking, imitation inhibition, humour appreciation, lie detection, vicarious experience and integrating top‐down and bottom‐up attention) (Santiesteban et al ., ; Sellaro et al ., ; Slaby et al ., ; Sowden et al ., ; Wu et al ., ; Ye et al ., ; Leloup et al ., ; Mai et al ., ; Vandenbroucke et al ., ). This study also improves on prior methodologies using high‐definition transcranial direct current stimulation (HD‐tDCS) rather than standard tDCS.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, using tDCS, several studies reported that the application of anodal or cathodal stimulation over the rTPJ could modulate the belief attribution ( Sellaro et al, 2015 ; Sowden et al, 2015 ; Ye et al, 2015 ). Sellaro et al (2015) found that participants who received anodal stimulation assigned less blame to accidental harms compared to participants who received cathodal or sham stimulation, emphasizing the role of rTPJ in mediating the belief attribution for moral judgements.…”
Section: Introductionmentioning
confidence: 99%